A compendium of photopigment peak sensitivities and visual spectral response curves of terrestrial wildlife to guide design of outdoor nighttime lighting - Longcore, Travis (Basic and applied ecology, 2023)
The presence and proportions of photopigments, which are responsible for the visual and physiological effects of light, vary between taxonomic groups. This leads to differing wavelength sensitivities ranging from ultraviolet (UV; <400 nm) to infrared (IR; >780 nm) and complicates the balancing of spectra used for outdoor lighting to maximize human visual performance while mitigating light pollution effects on wildlife. I developed a database of spectral response information for terrestrial wildlife to create generalized spectral response curves by taxonomic phylum, class, and order. Existing data on species visual sensitivity were collected from previously published research that used behavioral responses, electroretinograms (ERGs), and reflectance within the eye. Resulting summaries of photopigment peak sensitivities (n=968) and sensitivity curves (n=177) allow for general observations. Overall, longer wavelengths provide the highest possibility for supporting human visual performance at night while reducing intrusive overlap with the vision of other species, because many taxonomic groups are sensitive to light in the blue and into the ultraviolet. Comparison of average response curves at the class level and the spectral power distribution of lamps suggests that spectral tuning might reduce the apparency of the lowest correlated color temperature (CCT) lamps to insects, spiders, and non-human mammals the most, with substantial but smaller reductions for reptiles, birds, and amphibians. Spectral tuning, most simply by reducing CCT, should be considered an additional benefit to be used in concert with other mitigation measures such as dimming, shielding, and part-night lighting.